Are We Really Colour-blind? The Normalisation of Mass Female Incarceration. (October 2019) - Norris, Adele N.
The sharp rise in female incarceration rates in both the United States and New Zealand has received increased attention. Even more pressing are the racial disparities among imprisoned females. This exploratory case study examines 13 peer-reviewed articles published between 2005 and 2016 to understand the nature of colour-blind ideology in discussions of female imprisonment in New Zealand. Several themes emerged including the homogenisation of female prisoners. Apart from moderately linking vast racial disparities between incarcerated White women and Indigenous women to ill-defined colonial practices, contemporary explanations for the substantial racial disparities receive little attention. This article concludes that the absence of a critical lens toward contemporary forms and experiences of racism undergirding the mass criminalisation of Indigenous people perpetuates a colour blindness that in turn works to normalise mass female incarceration. Even in attempts to be unbiased, the way race/ethnicity, gender, age, and class are discussed in academic research exploring female incarceration seems to reflect the influential nature of controlling images rather than critique them.